THE ROLE OF VILLAGE GOVERNMENT IN MANAGING VILLAGE MARKETS (CASE STUDY OF KUALA SEMUNDAM MARKET, KUALA SEMUNDAM VILLAGE, BANDAR PETALANGAN DISTRICT, PELALAWAN REGENCY - Saputra, Andre; Hakim, Arif Rahman (Journal of Governance and Public Administration, 2025)
This study aims to analyze the role of the village government in the management of Kuala Semundam Market. The research method used is a qualitative descriptive approach, with data collection through in-depth interviews, participant observation, and documentation. The data were analyzed inductively using source and technique triangulation. The results indicate that the village government's role as a pioneer, innovator, and stabilizer in market management is not yet optimal, particularly in the poorly organized arrangement of vendors' trading areas and the inadequate market support facilities. The study concludes that village market management needs to be improved by better organizing vendors and developing more adequate market facilities to support community economic activities.   Keywords: Village Government, Market Management, Traditional Market, Village Role